Kerk in wording - Slot, Edward van 't (Kerk en theologie, 2024)
In response to ‘Tot heil van heel de werkelijkheid’, this article argues that the concepts of church and sacrament need to be considered more pneumatologically and eschatologically. Not only the concept of church ought to be understood in the sense that church is always ‘in the process of becoming’; the sacrament must also be understood in non-static event-like terms. The biblical concept from which the word ‘sacrament’ is derived, μυστήριον, is also a concept that underlines the dynamic (pneumatological, eschatological) character of the concept of church. With a reference to the ecclesiology of the young Bonhoeffer, this article also argues that a more dynamic concept of church creates space to fully appreciate the not so sacred elements in the existence of the church. In this dynamic existence, the church needs to receive the sacraments to strengthen faith; it is not itself a sacrament.